TAGUCHI METHOD IN ELECTRON BEAM WELDING WIDTH STUDY (Nonconventional Technologies Review, 2015)
The quality of the electron beam joints depends on a great number of parameters both of the workpiece material and of the beam. To reduce the input parameters one can use the Taguchi method. According to Taguchi method for the study of the influence of beam parameters and the welding parameters on the electron beam output parameters like weld width, one can reduce the number of experiences without losing the observations precision. An important advantage of this method is attention accorded to the possible interactions between factors highlight input into the process. The optimization of the system response involves finding the minimum of all possible answers in this case, the smallest weld width value.
Keywords: welding width; electron beam welding; Taguchi method